2016
DOI: 10.1165/rcmb.2015-0291oc
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Mouse Lung Exposures toStachybotrys chartarumShift Immune Response from Type 1 to Type 2

Abstract: After a single or multiple intratracheal instillations of Stachybotrys chartarum (S. chartarum or black mold) spores in BALB/c mice, we characterized cytokine production, metabolites, and inflammatory patterns by analyzing mouse bronchoalveolar lavage (BAL), lung tissue, and plasma. We found marked differences in BAL cell counts, especially large increases in lymphocytes and eosinophils in multipledosed mice. Formation of eosinophil-rich granulomas and airway goblet cell metaplasia were prevalent in the lungs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 65 publications
2
6
1
Order By: Relevance
“…Previous data from our laboratory and others demonstrate pulmonary pathology after S. chartarum exposure (24,25,30,31); however, the underlying mechanisms need further clarification. The aim of this study was to characterize the mechanisms contributing to the pulmonary immune responses after repeated exposure to S. chartarum.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Previous data from our laboratory and others demonstrate pulmonary pathology after S. chartarum exposure (24,25,30,31); however, the underlying mechanisms need further clarification. The aim of this study was to characterize the mechanisms contributing to the pulmonary immune responses after repeated exposure to S. chartarum.…”
mentioning
confidence: 74%
“…The present study used two different S. chartarum strains that included a high-fragmenting isolate and a low-fragmenting isolate. Aerosolized S. chartarum was repeatedly delivered to mice housed in a nose-only chamber to more closely mimic natural human exposure, a documented methodological advancement over studies using intranasal instillations, intratracheal instillations, or liquid aerosol inhalations (20)(21)(22)(23)(24)(25)(26). This model has been validated by characterizing the immune response and genetic profile after Aspergillus fumigatus exposure (27)(28)(29).…”
mentioning
confidence: 99%
“…These changes suggest a shift from type 1 inflammation after an acute exposure to type 2 inflammation after multiple exposures to S. chartarum. Eotaxin, vascular endothelial growth factor (VEGF), MIP-1α, MIP-1β, TNF-α, and the IL-8 analogs macrophage inflammatory protein-2 (MIP-2) and keratinocyte chemoattractant (KC), had more dramatic changes in multiple-than in single-dosed mice, and parallel the cytokines that characterize humans with histories of mold exposures versus unexposed control subjects [21].…”
Section: Discussionmentioning
confidence: 95%
“…Responses to mold are influenced by the genetics of both mold and mice. Rosenblum Lichtenstein and colleagues (9)(10)(11) showed that different strains of mice respond differently to mold. Croston and colleagues show that repeated exposures to two different strains of S. chartarum lead to different patterns of inflammation and arterial remodeling (1).…”
mentioning
confidence: 99%
“…Mold antigens and macrocyclic trichothecenes may elicit immune responses after repeated exposures (10,11). Importantly, the Croston paper describes repeatedly exposed mice.…”
mentioning
confidence: 99%